New Characterisation Techniques for Thin Film Antiferromagnetic Materials - Poole, S F (2023)
Antiferromagnets (AFMs), with their rise in prominence and the discovery of new effects, have led to growing interest in antiferromagnetic spintronics and their possible applications. Since AFMs have little or no stray fields and very low magnetic susceptibility, one of the biggest challenges faced by the field of AFM spintronics is the difficulty to manipulate and measure the magnetic structure of these systems. Most techniques capable of unambiguous detection of magnetic changes or domain structure require large facilities, and so the aim of the contained thesis was to support the development of new benchtop techniques capable of making such observations in AFMs.